2022-RA-1206-ESGO Selection of preexisting BRCA1/2-proficient tumor cells in BRCA1/2-driven tubo-ovarian carcinomas treated by neoadjuvant chemotherapy. (20th October 2022) - Imyanitov, Evgeny; Marchetti, Claudia; Sokolenko, Anna; Piermattei, Alessia; Gorodnova, Tatiana; Pavone, Matteo; Ivantsov, Alexandr; Scambia, Giovanni; Kuligina, Ekatherina; Berlev, Igor; Fagotti, Anna
Abstract : Introduction/Background: Tubo-ovarian carcinomas (OCs) are highly sensitive to platinum-based neoadjuvant chemotherapy (NACT) but almost never demonstrate complete pathologic response. Methodology: We analyzed paired primary and residual tumor tissues from 30 patients with hereditary BRCA1/2-driven OCs (BRCA1: 17; BRCA2: 13), who were treated by carboplatin/paclitaxel NACT (median number of cycles: 3, range 3–6). BRCA1/2 and TP53 genes were analyzed by the next-generation sequencing (NGS). The ratio between TP53 mutation-specific vs. wild-type reads was considered to monitor the proportion of tumor and non-tumor cells in the tissue sample. Assuming that all BRCA1/2 wild-type reads come from cells with retention of heterozygosity (ROH), one can calculate the percentage of cells with loss-of-heterozygosity (LOH). Excess of mutated vs. wild-type BRCA1/2 reads was interpreted as the LOH. We compared LOH in tumor tissues before and after NACT. Results: All 30 OCs had BRCA1/2 LOH in primary tumor and carried somatic TP53 mutation. Five (17%) tumor pairs showed transition from LOH to ROH during NACT presumably affecting all or the vast majority of residual tumor cells. Another 16 (53%) tumors demonstrated significant reduction of the percentage of tumor cells with LOH suggesting the expansion of BRCA1/2-proficient clones in the post-NACT tumor tissue. There were no signals of emergence of a second open reading frame (ORF) restoring BRCA1/2 mutation. Conclusion: Chemonaive BRCA1/2-driven carcinomas often contain a fraction of tumor cells with preserved BRCA1/2 heterozygosity. NACT can cause a selection of pre-existing BRCA1/2-proficient tumor cells, without gaining secondary reversal BRCA1/2 mutations.